Diagnóstico microbiológico de artritis séptica en niños usando botellas de hemocultivos como un método alternativo - Santiago Atehortúa (Asociación Colombiana de Infectología, 2020)
Introduction: Septic arthritis (SA) is defined as the infection of any joint space; it is more common in children under 5 years and its main cause is hematogenous dissemination. The etiological diagnosis is difficult in children, achieving isolation in less than half of the cases. The diagnostic performance of the blood culture bottle (BCB) was evaluated as an alternative medium for seeding synovial fluid compared to conventional media (CM). Methods: A prospective cohort survey was conducted in a third-level center from 2011-2016, in children aged 0 to 12 years with a clinical diagnosis of septic arthritis and availability of the two samples taken in surgery. Results: 60 patients were admitted, being 56% male, with a median age of 48 months and symptom time of 58 hours (48-192); 33.3% had a history of trauma; 30% received previous antibiotics. Affected joints: hip (44%), knee (28%), and ankle (18%). Blood cultures were taken in 39 patients (65%); of these, 19 (49%) were positive, all for S. aureus. Confirmation in synovial fluid was obtained by any method in 27 subjects (45%), positive in both: 21.6%, 13.3% in CM, and 10% in BCB. The most frequent microorganisms were: MSSA (21.6%), MRSA (8.3%), S. pyogenes (3.3%), MRSE (3.3%), S. pneumoniae (1.6%), N. meningitidis (1.6%). K. kingae was not isolated. The most commonly used antibiotic treatment was beta-lactams. The median of stay was 18 days (12-25.5), with a mortality of 3.3%. Conclusion: BCB are a complement to the conventional solid medium and increased the etiological confirmation of septic arthritis from 35 to 45%.